SOLUTION:
Step 1:
In this question, we are given the following:
Solve the system of equations y = 5x + 1 and -2x + 3y =-10 ?
What is the solution?
Step 2:
The solution to the systems of equations:
![\begin{gathered} y\text{ = 5x + 1 -- equation 1} \\ -2x\text{ + 3y = -10 -- equation 2} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ato6o24c0iw7sl4fa9csgtqx6i4ay1dx4w.png)
check:
Given y = -4 , x = -1
Let us put the values into the equation:
y = 5x + 1 and -2x + 3y = -10
![\begin{gathered} y\text{ = 5x + 1} \\ -4=5(-1)\text{ + 1} \\ -4=-5+1 \\ -4\text{ = - 4 (COR}\R ECT) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6d32e8umd8rx51xtjnzhncvzgtiqmfpt96.png)
![\begin{gathered} -2x+3y\text{ = -10} \\ -2(-1)+3(-4)_{}_{} \\ 2-12=-10\text{ (COR}\R ECT) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/pzdj99dkqxsamtaz8jkttkh0mf7vfy2b9m.png)
CONCLUSION:
The solution to the system of equations are:
![\begin{gathered} \text{x = -1} \\ y=-4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/bmz69phkxa2tyazbrmr2ch6en5wmlkbg10.png)